A qualitative study on integrated management systems in a non-leading country in certifications. (23rd February 2018) - Bernardo, Merce; Gotzamani, Katerina; Vouzas, Fotis; Casadesus, Marti
Abstract : The aim of this study is to analyse the integration of management systems (MSs) in a country with low certifications number and growth rate and propose a research agenda towards improving the competitiveness of organisations that implement multiple MSs. The main research questions focus on the implementation process itself and the effect of low level of national certification to the integration process. To serve this research purpose, an exploratory research is designed in Greece (a country with relatively low certification counts and rates to the ISO 9001 and ISO 14001 management standards). A case study approach is employed to enable deeper and comprehensive reasoning. A cross-case analysis is presented to explore patterns, similarities and differences among organisations. Findings show that four out of five organisations analysed are integrating its MSs at different levels, the integration methodology applied is similar for all organisations but audits are the most dissimilar aspect. This study is one of the first that addresses MSs' integration in Greece exploring contingency factors.